Goal-Directed Tableaux - Meheus, Joke; De Clercq, Kristof (The Many Sides of Logic, 2009)
This paper contains a new format for analytic tableaux, called goal-directed tableaux. Their main interest lies in the fact that the search for a closed tableau proceeds in a highly constrained way. The goal-directed tableaux do not form a complete decision method for propositional classical logic (because they do not sustain Ex Falso Quodlibet). For consistent sets of premises, however, they lead to the same results as the usual analytic tableaux for classical logic.